Autologous, lentivirus‐modified, T‐rapa cell "micropharmacies" for lysosomal storage disorders. Issue 4 (17th March 2022) - Nagree, Murtaza S; Felizardo, Tania C; Faber, Mary L; Rybova, Jitka; Rupar, C Anthony; Foley, S Ronan; Fuller, Maria; Fowler, Daniel H; Medin, Jeffrey A
Abstract: T cells are the current choice for many cell therapy applications. They are relatively easy to access, expand in culture, and genetically modify. Rapamycin‐conditioning ex vivo reprograms T cells, increasing their memory properties and capacity for survival, while reducing inflammatory potential and the amount of preparative conditioning required for engraftment. Rapamycin‐conditioned T cells have been tested in patients and deemed to be safe to administer in numerous settings, with reduced occurrence of infusion‐related adverse events. We demonstrate that ex vivo lentivirus‐modified, rapamycin‐conditioned CD4 + T cells can also act as next‐generation cellular delivery vehicles—that is, "micropharmacies"—to disseminate corrective enzymes for multiple lysosomal storage disorders. We evaluated the therapeutic potential of this treatment platform for Fabry, Gaucher, Farber, and Pompe diseases in vitro and in vivo . For example, such micropharmacies expressing α‐galactosidase A for treatment of Fabry disease were transplanted in mice where they provided functional enzyme in key affected tissues such as kidney and heart, facilitating clearance of pathogenic substrate after a single administration. Synopsis: The therapeutic potential of lentivirus (LV)‐modified, rapamycin‐conditioned CD4 + T cells (T‐Rapa) was evaluated. These T‐Rapa "micropharmacies" (TRaMs) can be used as next‐generation cellular delivery vehicles to treat Lysosomal Storage Disorders (LSDs) and other inherited disorders. LV vectors were developed to engineer overexpression and secretion of α‐galactosidase A (α‐gal A), glucocerebrosidase (GCase), acid ceramidase (ACDase), and acid α‐glucosidase (GAA). TRaMs generated from healthy donors (HDo) generated considerable levels of functional secreted enzyme when vector‐modified; and maintained secretion even when quiescent. TRaMs manufactured from Fabry patient donor cells (FDo) had high intracellular and secreted α‐gal A activities. α‐Gal A produced by TRaMs showed appropriate glycosylation and could be taken up by Fabry patient‐derived fibroblasts in vitro . Xenografted TRaMs reduced or, in some cases, normalized Gb3 and lyso‐Gb3 substrate levels in plasma and key tissues in a Fabry mouse model. Abstract : The therapeutic potential of lentivirus (LV)‐modified, rapamycin‐conditioned CD4 + T cells (T‐Rapa) was evaluated. These T‐Rapa "micropharmacies" (TRaMs) can be used as next‐generation cellular delivery vehicles to treat Lysosomal Storage Disorders (LSDs) and other inherited disorders.